Design and Analysis of an Interior Continuous Magnetic Gear Box Using Finite Element Method - Majidi, Behrooz; Milimonfared, Jafar (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Magnetic gears offer important potential benefits compared with mechanical gears such as reduced maintenance, improved reliability, inherent overload protection, and physical isolation between the input and output shafts. This paper presents the design and analysis of a novel structure of magnet gear, which named Interior Magnetic Gear (IMG) using neodymium-iron-boron magnets for the applications in which continuous ratio of gear box is useful such as wind generators, electric vehicles and etc. The analysis is performed by Finite Element Method (FEM) to predict output torque, speed and magnetic field distribution inside the gear box. The IMG made up of an inner rotor and an outer rotor. The inner rotor is similar to the rotor of a 3 phase wound rotor induction motor and the outer rotor consists of 6 PM poles. Both the inner rotor and the outer rotor can be employed as a low/high speed rotating part. The interior arrangement of PMs result many advantage such as low torque ripple. The simulation and analytical results are in good accord.